Biosurfactant Production by Bacteria Isolated from Hydrocarbon-impacted soil - Ismail, H.Y.; Isa, T.; Ngoshe, I.Y.; Gajere, H.M. (Bioremediation Science and Technology Research (e-ISSN 2289-5892), 2018)
Advancement in biotechnology and its industrial application has led to increased demand for biological compounds of microbial origin. Such compounds are biosurfactant and their application in different sectors is increasing despite some challenges. In the present study, the ability of bacterial species growing in hydrocarbon impacted soil to produce biosurfactants was investigated with a view to isolate competent biosurfactant producers with desirable qualities for a large scale biosurfactant production. Soil samples contaminated with different kinds of hydrocarbon were collected from Mechanic workshop (MW) and Mai-kose (MK) area in Maiduguri Metropolis, Nigeria. Soil samples were cultured on nutrient agar and mineral salt agar by pour plate technique for enumeration of viable bacteria and isolation of oil utilising bacteria respectively. Samples from MW were observed to harbour fewer bacteria than MK area with 7.3 ×107 CFU/g and 4.0×108 CFU/g respectively. Fifteen bacterial species were isolated and identified to belong to the genus Pseudomonas using cultural, morphological and biochemical characteristics. The species were P. aeruginosa, P. citronellolis and P. mendocina with 66.7%, 26.6% and 6.6% rate of occurrence. A preliminary investigation for the isolates’ ability to produce biosurfactants using haemolysis and hydrocarbon degradation tests revealed that all the isolates were haemolytic on blood agar and can utilise vegetable oil at different magnitudes. Biosurfactant assay using broth culture supernatants showed that all the isolates were able to produce surfactants that collapsed oil drop within the interval of 10-20 min and Pseudomonas citronellolis WB4 was most efficient in this respect (t = 10 min). With regards to oil spreading assay, P. aeruginosa KB1 produced largest diameter (d) of 4.21 cm after 15 min compared to other species (dav. = 3.44cm average tav. = 13 min). After 24 hrs of emulsion formation, it was observed that P. aeruginosa WB5 (E24 = 70.45%) and P. citronellolis WB4 (E24 = 70.35%) have the highest emulsification indexes (range 70.45% - 43.75%). Therefore, all isolates in this study were biosurfactant producers with P. citronellolis WB4 being the most suitable candidate for large-scale biosurfactant production. Hence, further studies are recommended to harness its full potentials.